MEMINIMALISIR KECANDUAN MELALUI KONSEP REHABILITASI BAGI PECANDU DAN KORBAN PENYALAHGUNA NARKOTIKA - Darmawati Darmawati; Asriadi Zainuddin (Jurnal Restorative Justice, 2022)
Narcotics addicts from a legal perspective are criminal offenders, but if we look more closely it can be said that they are victims of narcotics illicit trafficking associations. Narcotics addicts are prisoners who require special treatment in the form of therapy to eliminate and stop the intention to consume narcotics and replace them with other beneficial behaviors. Narcotics addicts require different handling in terms of the criminal process. Law Number 35 of 2009 concerning Narcotics through Article 59 mandates the responsibility to undergo treatment and treatment or rehabilitation for addicts. The purpose of this study was to determine the flow of rehabilitation for addicts and victims of narcotics abusers and to find a concept of rehabilitation for addicts and victims of narcotics abusers in minimizing dependence on illegal drugs. The type of research used in this study is a combination of normative legal research and legal research. empirical. The rehabilitation of narcotics prisoners in Gorontalo City is still being carried out in general prisons while still coordinating with the National Narcotics Agency and the Tombulilato Hospital. The concept in terms of implementing rehabilitation to minimize drug dependence is by grouping based on the level of addiction of narcotics prisoners based on the results of the initial assessment that has been carried out and supervising the post-rehabilitation implementation of narcotic clients to see whether the client has completely recovered or not.